Rzeczy "dawne" i rzeczy "nowe" w wypowiedziach Deuteroizajasza - Stachowiak, Lech (The Biblical Annals, 2017)
Yahweh's creative power, and the saving action which is closely linked with it, are among His most characteristic attributes. For Deutero-Isaiah, God manifests His creative power in history and in His saving action. "Old" things denote the history of salvation so far, while "new" things denote a new exodus from slavery. The theme of "old" and "new" things plays an especially important part in the following texts: Is. 41, 22-23; 42, 9; 43, 9. 18-19; 46, 9-10; 48, 3-6. In their exegetic analysis particular attention is paid to the motif of "old" and "new" things. The above texts show that history does not unfold in a random fashion, but is the realization of the prior word of Yahweh. God’s guidance lends things special unity. In this way He, "the first" and "the last" (Is. 41, 4), proclaims the beginning and the end, makes a promise and fulfils it, proving His godhead. He was conscious of His intentions from the beginning and was able to carry them out in full.